A Role for Matrix Metalloproteases in Antidepressant Efficacy - Alaiyed, Seham; Conant, Katherine (Frontiers in Molecular Neuroscience, 2019)
Major depressive disorder is a debilitating condition that affects approximately 15 % of the U.S. population. Though the neurophysiological mechanisms that underlie this disorder are not completely understood, both human and rodent studies suggest that excitatory/inhibitory (E/I) balance is reduced with the depressive phenotype. In contrast, antidepressant efficacy in responsive individuals correlates with increased excitatory neurotransmission in select brain regions, suggesting that the restoration of E/I balance may improve mood. Enhanced excitatory transmission can occur through mechanisms including increased dendritic arborization and synapse formation in pyramidal neurons. Reduced activity of inhibitory neurons may also contribute to antidepressant efficacy. Consistent with this possibility, the fast-acting antidepressant ketamine may act by selective inhibition of glutamatergic input to GABA releasing parvalbumin (PV)-expressing interneurons. Recent work has also shown that a negative allosteric modulator of the GABA-A receptor  subunit can improve depression-related behavior. PV-expressing interneurons are thought to represent critical pacemakers for synchronous network events. These neurons also represent the predominant GABAergic neuronal population that is enveloped by the perineuronal net (PNN), a lattice-like structure that is thought to stabilize glutamatergic input to this cell type. Disruption of the PNN reduces PV excitability and increases pyramidal cell excitability. Various antidepressant medications increase the expression of matrix metalloproteinases (MMPs), enzymes that can increase pyramidal cell dendritic arborization and spine formation. MMPs can also cleave PNN proteins to reduce PV neuron-mediated inhibition. The present review will focus on mechanisms that may underlie antidepressant efficacy, with a focus on monoamines as facilitators of increased matrix metalloprotease (MMP) expression and activation. Discussion will include MMP-dependent effects on pyramidal cell structure and function, as well as MMP-dependent effects on PV expressing interneurons. We conclude with discussion of antidepressant use for those at risk for Alzheimer’s disease, and we also highlight areas for further study.